Upper body kinematic predictors of ball velocity during out of hand kicking in international level rugby league kickers - Sinclair, J.; Taylor, P. J.; Atkins, S.; Hobbs, S. J. (International Journal of Sports Science and Engineering, 2013)
Out of hand punt kicking is integral the attacking and defensive elements of rugby league and a coveted aspect of any player's skill set is the ability to kick the ball with high linear velocity. This study aimed to identify the important technical aspects of kicking linked to the generation of ball velocity using regression analyses. Maximal out of hand kicks were obtained from six international standard rugby league kickers using a 3-D motion capture system sampling at 250Hz. Upper body 3-D kinematics were obtained. Regression analyses with ball velocity as criterion was used to identify the upper body kinematic parameters associated with the development of ball velocity. The regression model yielded an Adj R2=0.81, p.0.01. A single discrete variable: Sagittal plane torso rotation at ball impact. This suggests that upper body kicking mechanics have a strong influence on ball velocity and potentially overall kicking performance. Therefore it is recommended that players be exposed to coaching and strength techniques geared towards the modification of kicking mechanics specific to this study.